Alih Kode Dan Campur Kode Dalam Film Komedi Fantas “Penguasa Dunia” - Putri Wahyu Pramudita; Umi Marfiatin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Code-switching and code mixing can not only be found in direct speech but also in social media such as videos on the YouTube platform, one of which can be found on the Lula Studio YouTube video channel entitled